BREAST ULTRASOUND IN THE INTERIOR OF THE STATE OF SANTA CATARINA, BRAZIL - Marinho, Luiz Alberto Barcellos (Mastology, 2018)
Breast ultrasound is an essential tool in Mastology. This technology can help in the diagnosis of lesions affecting the mammary gland, identifying both benign and malignant tumors. However, ultrasound examination has precise indications in medical practice; and should be indicated cautiously, as one should not think it can tackle all diagnoses of the breast. In this paper, the author assesses 197 breast ultrasounds in the city of Chapecó, Santa Catarina, Brazil. The author reports lack of clinical criteria in many indications of ultrasound examination by health professionals at Basic Health Units of the city.